The first decade of web-based sports injury surveillance: Descriptive epidemiology of injuries in US High School Girls' Field Hockey (2008-2009 through 2013-2014) and National Collegiate Athletic Association Women's Field Hockey (2004-2005 through 2013-2014) - Lynall, R. C.; Gardner, E. C.; Paolucci,J.; Currie, D. W.; Knowles, S. B.; Pierpoint, L. A.; Wasserman, E. B.; Dompier, T. P.; Comstock, R. D.; Marshall, S. W.; Kerr, Z. Y. (Journal of Athletic Training, 2018)
Context: The advent of Web-based sports injury surveillance via programs such as the High School Reporting Information Online system and the National Collegiate Athletic Association Injury Surveillance Program has aided the acquisition of data for girls' and women's field hockey injuries.